Report and deport: Public vigilance and migration policing in Australia - Walsh, James (Theoretical criminology, 2020)
Recent escalations in migration control involve the criminalization of non-citizens. In assessing this punitive turn criminologists have highlighted drastic expansions in state sovereignty and coercion. Focusing on the Australian context, this article examines a less noticed trend: the civilianization of migration policing. To facilitate irregular migrants’ removal the government has created tip-lines that encourage private citizens to conduct surveillance and anonymously ‘dob-in’ or report unlawful non-citizens. Approaching the initiative as a distinct responsibilization strategy that enrolls the entire citizen body as policing agents, this article explores its instrumental and symbolic goals, whether expanding official gazes or restoring an exclusive sense of national citizenship. Assessing the functions and effects of public vigilance reveals important tensions and ambiguities within the responsibilization process. In particular the case of participatory surveillance demonstrates how ‘adaptive’ approaches to order maintenance are not external to, but potentially promote and perpetuate, punitive forms of sovereign power.